2020
DOI: 10.1186/s13287-020-01613-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome differences in adipose stromal cells derived from pre- and postmenopausal women

Abstract: Background: As the population ages, an increasing number of postmenopausal women are donors of adipose stromal cells (ASCs) and may benefit from autologous ASC-related treatments. However, the effect of menopausal status on ASCs has not been investigated. Methods: RNA sequencing data were downloaded, and differentially expressed genes (DEGs) were identified. Hierarchical clustering, Gene Ontology, and pathway analyses were applied to the DEGs. Two gene coexpression network analysis approaches were applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It is interesting to note that TAM treated patients are mostly similar to post-menopausal subjects, in terms of differentiation capacity, compare to pre-menopausal ones. A recent study shown that at a transcriptome level ASCs from pre-e post-menopausal women are different (Xie et al, 2020), this could, at least partially, explaining the trend and why TAM-treated ASCs and ASCs from post-menopausal subjects appear to be more similar and slightly different from pre-menopausal one. At the best our knowledge our study is the first implying ex vivo ASCs from TAM-treated patients and pre-and post-menopausal subjects, indeed in light of the trend we found and the above-mentioned study, further studies to better clarify this point are needed.…”
Section: Discussionmentioning
confidence: 96%
“…It is interesting to note that TAM treated patients are mostly similar to post-menopausal subjects, in terms of differentiation capacity, compare to pre-menopausal ones. A recent study shown that at a transcriptome level ASCs from pre-e post-menopausal women are different (Xie et al, 2020), this could, at least partially, explaining the trend and why TAM-treated ASCs and ASCs from post-menopausal subjects appear to be more similar and slightly different from pre-menopausal one. At the best our knowledge our study is the first implying ex vivo ASCs from TAM-treated patients and pre-and post-menopausal subjects, indeed in light of the trend we found and the above-mentioned study, further studies to better clarify this point are needed.…”
Section: Discussionmentioning
confidence: 96%